Energy 2050 : making the transition to a secure low carbon energy system - Ekins, Paul; Skea, Jim; Winskel, Mark (Earthscan, 2010)
The United Kingdom is committed to reducing its greenhouse gas emissions by at least 80 per cent by 2050. This book explores in detail those factors which could help or hinder the attainment of the UK's climate change targets, and how these factors interact with the parallel objective of maintaining a robust and secure energy system